Development of an animal disease lab-on-chip for the detection of multiple animal disease pathogens of economic and/or public health importance. - Nurlilah Ab.Rahman. (2013)
This Thesis investigated the optimization efforts undertaken during the Final Year Project in deriving the conditions, parameters and variables associated with a multiplex asymmetric polymerase chain reaction (MAPCR)-based oligonucleotide microarray assay that defines the Lab-on-Chip (LOC) platform currently in development by the Agri-Food & Veterinary Authority (AVA) of Singapore for multiple zoonoses detection. For a detection system of 10-15 selected viral and bacterial pathogens, investigations were carried out to select amplification kits suitable for both the avian influenza and bacteria Panels, to derive the optimal asymmetric primer concentrations for each pathogen target within the multiplex system and to assess extent of primer cross-reactivity and specificity. Optimizations were successfully carried out at 1E5 plasmid copy number, roughly translated to concentrations in the picogram levels. The results and findings emphasize the high sensitivity and specificity of the LOC platform being developed. Lastly, this Thesis evaluated two multiple-pathogen detection platforms currently in use and compared their benefits and drawbacks with the LOC being developed.